A bi-objective stochastic single facility location model for a supermarket [electronic resource] - Arousha Haghighian Roudsari, 1986- (2013)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2013